Bi-fluid cooling effect on electrical characteristics of flexible photovoltaic panel - Nurul Shahirah Rukman; Ahmad Fudholi; Putri Adia Utari; Cheku Nurul Aisyah; Andri Joko Purwanto; Rakhmad Indra Pramana; Erie Martides; Ant. Ardath Kristi; Nilofar Asim; Mohammad Hossein Yazdi; Hazim Moria; Husam Abdulrasool Hasan; Zeki Ahmed Darwish (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2021)
A photovoltaic (PV) system integrated with a bi-fluid cooling mechanism, which is known as photovoltaic thermal (PVT) system, was investigated. The electrical characteristics of flexible solar panel were evaluated for PV and PV with bi-fluid (air and water) cooling system. The integration of monocrystalline flexible solar panel into both systems was tested under a fixed solar radiation of 800 W/m2. A total of 0.04–0.10 kg/s of air flow was utilised in PV with cooling system with a fixed water mass flow rate of 0.025 kg/s. The efficiencies of flexible panel for PV and PV with cooling system were explored. For PV with bi-fluid flow, the highest obtained efficiency of module was 15.95% when 0.08 kg/s of air and 0.025 kg/s of water were allowed to flow through the cooling system. Compared with PV without cooling mechanism, the highest efficiency of module was 13.35% under same solar radiation. Current–voltage and power graphs were also plotted to present the electrical characteristics (current, voltage and power) generated by both systems.